2017
DOI: 10.3390/rel8040062
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping as Moderator of Psychological Responses to Stressful Events: A Longitudinal Study

Abstract: Abstract:The aim of this study was to evaluate the association of positive and negative religious coping with posttraumatic symptoms (PTS) and growth (PTG). Their moderating role was also examined among predictors such as social support and the subjective severity of event with PTS and PTG. Two hundred and eleven Chilean adults (58.3% women) of 18 years and older who had been exposed to highly stressful were surveyed. The Brief-RCOPE, the Brief-COPE subscale of social support, the Subjective Severity of Event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 37 publications
2
17
0
3
Order By: Relevance
“…This view was also reported by Ahern and Norris 30 . However, a more comprehensive study by Ahlers, Mezulis and Hudson found that religion was only a buffer to stress in individuals with high religious commitment, which may perhaps only be relevant to the participants attended religious activities very frequently 56 .…”
Section: The Resilience Levels and Health Behaviours Of Participantsmentioning
confidence: 97%
“…This view was also reported by Ahern and Norris 30 . However, a more comprehensive study by Ahlers, Mezulis and Hudson found that religion was only a buffer to stress in individuals with high religious commitment, which may perhaps only be relevant to the participants attended religious activities very frequently 56 .…”
Section: The Resilience Levels and Health Behaviours Of Participantsmentioning
confidence: 97%
“…However, the nature of the religious coping utilized appears to influence response to trauma. In a longitudinal examination of Chilean adults who experienced a recent stressful event, including but not limited to natural disasters, positive religious coping was related to posttraumatic symptoms whereas negative religious coping was related to posttraumatic growth (García et al, 2017). Baral and Bhagawati (2019) discovered that individuals who developed PTSD after an earthquake in Nepal were more likely to utilize passive coping, religious coping, and substance use coping; whereas, those who did not develop PTSD engaged in more active and self-distraction coping.…”
Section: Religious Coping and Natural Disastersmentioning
confidence: 99%
“…Może też wskazywać na przeżywany przez nauczyciela kryzys. Stosowanie NRC może być zatem sygnałem, że osoba potrzebuje pomocy (García, Páez, Reyes-Reyes, Álvarez, 2017;Pargament i in., 1998;Pargament i in., 2011).…”
Section: Podsumowanie I Dyskusjaunclassified